Workshop Kerajinan Kulit Jagung Berbasis Media Sosial di Desa Pematang Panjang - Rahma Pitria Ningsih; Fathinatush Shalihah; Sulaiman Sulaiman; Rahmah Rahmah; Mitra Yadiannur (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program was motivated by the limited utilization of corn husk waste as a valuable material and the suboptimal use of social media as a learning and promotional tool for village-based creative products. The program aimed to improve creativity, productive skills, and digital marketing literacy among residents of Pematang Panjang Village, Sungai Tabuk District, Banjar Regency. A participatory empowerment approach was applied through team coordination, partner problem identification, solution formulation, hands-on workshop implementation, and result publication. The activity was conducted on June 27, 2026, and involved 25 participants. The workshop covered the concept of eco-friendly products, techniques for processing corn husks into flower bouquets and decorative crafts, product design development, simple packaging, and the use of social media for inspiration and promotion. The results showed that participants were able to produce corn husk handicrafts, understand the economic potential of agricultural waste, and gain initial insight into digital promotion. This program is significant as an initial model of village creative economic empowerment based on local skills and digital literacy.